Islamic Financial Product Literacy in the New Normal Era - Devy Mawarnie Puspitasari; Eristy Minda Utami; Lia Amaliwiati (Universitas Serang Raya, 2023)
Starting from the health crisis, the Covid-19 pandemic has had a domino effect on social, economic and financial aspects. The economy experienced a slowdown in line with the decline in people's purchasing power due to decreased income, no income and economic activity. Various efforts were made by the government to restore the national economy by adopting comprehensive fiscal and monetary policies. The government also allocates APBN funds for economic recovery up to Rp. 695.2 Trillion. The economic recovery began to grow from the banking sector with assets of 15.6% (yoy) in May 2021 until the Islamic capital market recorded 9.3% investor growth in the first quarter of 2021. Understanding of Islamic banking products in the community that is not yet optimal requires socialization of understanding of banking products Sharia in the new normal era. It is hoped that through socialization it can increase public literacy to accelerate economic recovery through Islamic financial products. Partners of this community service activity are Widyatama University students, Bandung. The flow of this community service activity consists of 3 stages starting from problem identification, implementation of activities, and evaluation of implementation. The results of this activity show that partners have increased understanding of Islamic financial products and there is a desire to make Sharia products their financial instrument.